2017
DOI: 10.1039/c6cc10307c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a chiral anthracene cation radical: X-ray crystallography and computational interrogation of its racemization

Abstract: Chiral cation-radical salts hold significant promise as charge-transfer materials, chiroptical switches, and electron-transfer catalysts for enantioselective synthesis. Herein we demonstrate that the readily-available chiral 9,10-diphenyleanthracene derivative (i.e. SANT) forms a robust cation radical, whose structure was elucidated by X-ray crystallography and DFT calculations. While SANT was observed to racemize on a timescale (t1/2 ) of 1.1 hours, a computational conformational search and kinetic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was shown that 40% of the HF exchange provides a balanced description of the electronic structure of the poly- p -phenylene cation radicals similarly to that shown by Kaupp and co-workers for a reliable description of the another class of organic mixed-valence systems. Indeed, modified B1LYP-40/6-31G­(d) functional performed exceptionally well in reproducing the experimental redox/optoelectronic properties of a variety of poly- p -phenylene- , and polyfluorene-based wires and other PAHs. , …”
Section: Results and Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It was shown that 40% of the HF exchange provides a balanced description of the electronic structure of the poly- p -phenylene cation radicals similarly to that shown by Kaupp and co-workers for a reliable description of the another class of organic mixed-valence systems. Indeed, modified B1LYP-40/6-31G­(d) functional performed exceptionally well in reproducing the experimental redox/optoelectronic properties of a variety of poly- p -phenylene- , and polyfluorene-based wires and other PAHs. , …”
Section: Results and Discussionmentioning
confidence: 91%
“…The importance of this finding is recognized in light of prior works that have shown, through X-ray structural analysis of PAH cation radicals, that contraction/elongation of the C−C bonds upon 1-e − oxidation track in accordance with the nodal structure of HOMO (i.e., bonds with bonding HOMO lobes undergo elongations, whereas the bonds with antibonding HOMO lobes undergo contractions). 28,29,38 Moreover, the experimental bond length changes in various PAH cation radicals can be fully reproduced by DFT calculations and the calculated spin/charge distributions in these cation radicals closely resemble the HOMO density distributions. 28,29,38 Indeed, the calculated spin-density distributions (Figure 7A) correspond to phenanthrene-like orbital in DBC +• , m-DBC +• and m/p-DBC +• and biphenyl-like orbital in p-DBC +• , in accordance with the nodal arrangement of HOMOs displayed in Figure 5.…”
Section: ■ Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this context, we introduced a customized version of B1LYP functional with 40% of HF exchange term (i.e., B1LYP-40) where the amount of HF was empirically adjusted to accurately reproduce oxidation potentials and the cation radical excitation energies of poly­( p -phenylene)­s. Remarkably, it was shown in multiple studies that B1LYP-40/6-31G­(d) performs exceptionally well in reproducing the experimental redox/optoelectronic properties of a variety of poly­( p -phenylene)-based wires, ,, other PAHs, , and π-stacked assemblies that were not included in the original training set. In a recent study, we also showed on several selected PAHs that time-dependent DFT paired with B1LYP-40 functional provides excitation energies and orbitals involved in the excitation that are consistent with those obtained using a highly reliable EOM-IP-CCSD method.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%